2004
DOI: 10.1096/fj.04-1700fje
|View full text |Cite
|
Sign up to set email alerts
|

Notch 1 and 3 receptors modulate vascular smooth muscle cell growth, apoptosis and migration via a CBF‐1/RBP‐Jk dependent pathway

Abstract: Vascular smooth muscle cell (SMC) fate decisions (cell growth, migration, and apoptosis) are fundamental features in the pathogenesis of vascular disease. We investigated the role of Notch 1 and 3 receptor signaling in controlling adult SMC fate in vitro by establishing that hairy enhancer of split (hes-1 and -5) and related hrt's (hrt-1, -2, and -3) are direct downstream target genes of Notch 1 and 3 receptors in SMC and identified an essential role for nuclear protein CBF-1/RBP-Jk in their regulation. Consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(151 citation statements)
references
References 57 publications
(42 reference statements)
9
138
2
2
Order By: Relevance
“…Furthermore, Notch-1 and Notch-3 appear to behave very similarly in terms of interaction with the conventional Notch DSL ligands, i.e. Jagged1 and Delta-like-1 (35). Our data show that the EGF-like repeats 13-33 in Notch-3 are sufficient for interaction with YB-1.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, Notch-1 and Notch-3 appear to behave very similarly in terms of interaction with the conventional Notch DSL ligands, i.e. Jagged1 and Delta-like-1 (35). Our data show that the EGF-like repeats 13-33 in Notch-3 are sufficient for interaction with YB-1.…”
Section: Discussionmentioning
confidence: 56%
“…As described by Campos et al (2002), also here Notch3 modulates c-FLIP expression by the ERK/ mitogen-activated protein kinase (MAPK) cascade. In a very recent study (Sweeney et al, 2004) the capacity of Notch1 and Notch3 to modulate apoptosis in VSMC by the classic RBP-Jk-dependent mechanism was shown. In another paper, Wang et al (2003) showed that inhibition of apoptosis in VSMC might occur by mechanisms not involving c-FLIP.…”
Section: The Effects Of Notch Signallingmentioning
confidence: 98%
“…There is some emerging genetic evidence to suggest the existence of an RBP-J-independent ('non-canonical') pathway through which Notch receptor signaling may exert some influence (Talora et al, 2008). However, the key effectors implicated in medulloblastoma growth, Hes1 and Hes5 are clearly both 'canonical' Notch targets (Jarriault et al, 1995(Jarriault et al, , 1998Sweeney et al, 2004;Ong et al, 2006). Given the number of ligands and receptors potentially having a role in the cerebellum, here we took the approach of blocking Notch signaling by deleting the common pathway effector RBP-J, which has proved to be a highly effective strategy in analyses of Notch signaling (Fujikura et al, 2006;Komine et al, 2007).…”
Section: Introductionmentioning
confidence: 99%